Antigenicity and protective efficacy of a Leishmania amastigote-specific protein, member of the super-oxygenase family, against visceral leishmaniasis. - Vivian T Martins; Miguel A Chávez-Fumagalli; Lourena E Costa; Adriana M C Canavaci; Adriana M C C Martins; Paula S Lage; Daniela P Lage; Mariana C Duarte; Diogo G Valadares; Rubens D M Magalhães; Tatiana G Ribeiro; Ronaldo A P Nagem; et al. (Public Library of Science (PLoS), 2013)
Background The present study aimed to evaluate a hypothetical Leishmania amastigote-specific protein (LiHyp1), previously identified by an immunoproteomic approach performed in Leishmania infantum, which showed homology to the super-oxygenase gene family, attempting to select a new candidate antigen for specific serodiagnosis, as well as to compose a vaccine against VL. Methodology/principal findings The LiHyp1 DNA sequence was cloned; the recombinant protein (rLiHyp1) was purified and evaluated for its antigenicity and immunogenicity. The rLiHyp1 protein was recognized by antibodies from sera of asymptomatic and symptomatic animals with canine visceral leishmaniasis (CVL), but presented no cross-reactivity with sera of dogs vaccinated with Leish-Tec, a Brazilian commercial vaccine; with Chagas' disease or healthy animals. In addition, the immunogenicity and protective efficacy of rLiHyp1 plus saponin was evaluated in BALB/c mice challenged subcutaneously with virulent L. infantum promastigotes. rLiHyp1 plus saponin vaccinated mice showed a high and specific production of IFN-γ, IL-12, and GM-CSF after in vitro stimulation with the recombinant protein. Immunized and infected mice, as compared to the control groups (saline and saponin), showed significant reductions in the number of parasites found in the liver, spleen, bone marrow, and in the paws' draining lymph nodes. Protection was associated with an IL-12-dependent production of IFN-γ, produced mainly by CD4 T cells. In these mice, a decrease in the parasite-mediated IL-4 and IL-10 response could also be observed. Conclusions/significance The present study showed that this Leishmania oxygenase amastigote-specific protein can be used for a more sensitive and specific serodiagnosis of asymptomatic and symptomatic CVL and, when combined with a Th1-type adjuvant, can also be employ as a candidate antigen to develop vaccines against VL.